Dinâmicas socioespaciais e arranjos produtivos locais na Ilha de Lençóis: entre o cotidiano e a experiência turística - CAMPOS, Samya Cristina dos Santos (2023)
Thinking about traditional communities evokes the notion of strong preservation of cultural identity, a reality that fosters the interest in commercially exploiting these spaces through economic activities, such as tourism. This utilization may generate various impacts, both positive and negative, depending on how it is established in a specific locality. This study was conceptualized with the aim of investigating the presence of tourist activity utilizing the business model of Productive Local Arrangements in Ilha de Lençóis, located in Cururupu – MA. It is a traditional fishing and beach community that is part of the Marine Extractive Reserve of Cururupu. The study primarily examines local development and the potential effects on the dynamics of life in this area. This research was conducted through a review of relevant literature and field visits to explore the community's characteristics, how the existing tourism is perceived by the residents, and their perspectives regarding the future with the presence and development of this activity. To provide a comprehensive study, an action plan was created for the structuring of the Local Productive Arrangement, following the community's expression of interest in this model. The general objective of this research is to gain insight into the coexistence of identity and cultural preservation alongside socioeconomic development through tourism, within the same context.